Flexural behavior and durability of reinforced concrete beams with seawater, sulfate-resistant cement, and glass fiber-reinforced polymer reinforcement - Abdelrahman Abushanab (17268940) (2025)
Seawater has recently been proposed for concrete manufacturing as a sustainable alternative to fresh water. However, seawater degrades the concrete properties at later ages. Accordingly, this study experimentally and analytically investigated the flexural behavior and durability of 9 concrete beams reinforced with glass fiber-reinforced polymer (GFRP) reinforcement and made with 3 seawater replacement ratios (0 %, 50 %, and 100 %), 2 types of cement (ordinary Portlandite and sulfate-resistant cement), and 2 types of curing water (fresh water and seawater). The beams were prepared with dimensions of 200 × 500 × 2200 mm and tested after exposure to seawater for 6 months. The results demonstrated that incorporating seawater and sulfate-resistant cement simultaneously improved the 28-day mechanical properties of concrete by about 16 % compared to those made entirely with fresh water. Likewise, beams made with 100 % seawater and sulfate-resistant cement recorded an improvement of 23 % in the load-carrying capacity and 80 % in the energy absorption compared to beams with fresh water. In addition, the beams made with seawater and sulfate-resistant cement showed no difference in the failure mode and flexural properties after conditioning in seawater for 180 days as compared to the reference beam. Analytically, ACI 440.11–22 achieved the best moment capacity prediction of the tested beams with an average, standard deviation, and coefficient of variance of experimental-to-predicted moment ratios of 1.26, 0.11, and 8.75 %, respectively. Other Information Published in: Engineering Structures License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.engstruct.2025.120204